An Economic Analysis of Collaboration Between Gompeting Firms - Eberhard Stickel (Kredit und Kapital, 2004)
Eine ökonomische Analyse der Kooperation zwischen Wettbewerbern Kooperation spielt nicht zuletzt unter dem Aspekt ständig steigender Entwicklungskosten eine wichtige Rolle bei der Entwicklung von Informationssystemen. Entscheidungsträger sollten deshalb die ökonomischen Effekte derartiger Entwicklungspartnerschaften verstehen, um rationale Entscheidungen zu fällen. Im Rahmen der Arbeit werden die ökonomischen Effekte von Entwicklungspartnerschaften zwischen Wettbewerbern detailliert analysiert. Bei der gemeinsamen Entwicklungsarbeit wird natürlich oft wertvolles Wissen an Konkurrenten weitergegeben. Dies spricht gegen Kooperation, während das Einsparen von Entwicklungskosten eher dafür spricht. Insofern ist nicht klar, ob Kooperationen zwischen Wettbewerbern sinnvoll sein können. In der Literatur werden zahlreiche Modelle diskutiert. Die wichtigsten Faktoren, die eine Kooperationsentscheidung beeinflussen, sind dabei Markt- und Produktstruktur, Art und Umfang der vorherrschenden Unsicherheit sowie die Risikopräferenzen der Entscheidungsträger. Die in der Literatur diskutierten Ergebnisse unterscheiden sich dabei je nachdem, wie man diese Faktoren kombiniert. Der aus Sicht der Praxis wichtigste Fall liegt bei oligopolistischer Marktstruktur, heterogenen Produkten und risikoaversen Entscheidungsträgern, die Nutzenmaximierung betreiben, vor. Dieser Fall wurde nicht zuletzt aufgrund seiner Komplexität bisher nicht umfassend analysiert und ist Gegenstand dieser Arbeit. Die Analyse erfolgt anhand eines formalen Optimierungsmodells, das die Bestimmung von geschlossenen Lösungen erlaubt. Das Modell kann in verschiedene Richtungen erweitert und so besser an die Realität angepasst werden – – An Economic Analysis of Collaboration Between Competing Firms To understand adoption of collaborative systems, it is of great importance to know about economical effects of collaboration itself. Decision makers should be able to value potential drawbacks and advantages of collaboration. Based on this estimation, the potential of collaborative technology may be determined. Throughout the paper we are interested in the effects of collaboration across a firm's boundary. There is vast literature on economical effects of collaboration among companies situated along different phases of the value chain. At least in economical terms this seems to be a well understood problem. The situation is different with respect to collaboration between competing companies. Strategies of firms may be seen as a mixture of cost reduction, product differentiation and improvement of decision making and/or planning. In this context information technology may help a firm to create sustaining competitive advantages over competitors. It is less clear whether collaboration is of any use in such an environment. According to the economics literature, the most important factors affecting benefits of collaboration are market structure, kind and degree of uncertainty faced by the firms, their risk preferences and the type(s) of product(s) offered (homogeneous or het- erogeneous products). The results reported depend on the way these factors are combined. They partially contradict each other. In this paper we will analyze the most relevant case of an oligopoly with differentiated products, demand uncertainty and risk averse managers. This combination has not yet been examined in detail, although it is the most realistic case. We will present a microeconomic model and use techniques from game theory for the analysis. The way the model is constructed will allow the derivation of closed-form solutions. Results indicating whether collaboration in various areas makes sense will be obtained. This makes it possible to judge the potential of available collaborative technology. The simple model presented may be extended in a variety of ways. Some directions for possible generalization are indicated. (JEL CO, C70, L10)
Keywords: CO; C70; L10; 330